A novel ceramic-based thin-film composite nanofiltration membrane with enhanced performance and regeneration potential. (15th May 2022) - Xu, Daliang; Luo, Xinsheng; Jin, Pengrui; Zhu, Junyong; Zhang, Xin; Zheng, Junfeng; Yang, Liu; Zhu, Xuewu; Liang, Heng; Van der Bruggen, Bart
Highlights: An interwoven net structure was constructed on the ceramic substrate. The ceramic-based membrane showed mechanical and thermal stability. The ceramic-based membrane exhibited excellent permeance and salt rejection. The membrane had a regeneration ability to prolong the lifetime and lower the cost. Abstract: The rational design of a ceramic-based nanofiltration membrane remains a significant challenge due to its performance and fabrication cost. Herein, we report a high-performance ceramic-based thin-film composite (TFC) membrane fabricated via a typical interfacial polymerization on an interwoven net substrate assembled by titanium dioxide (TiO2 ) nanowires. The chemical properties and morphologies were systematically investigated for ceramic substrates and their corresponding TFC membranes. Due to the significantly improved hydrophilicity of the TiO2 framework, more reactive amine monomers were uniformly adsorbed on the modified surface of the ceramic substrate, yielding an ultrathin polyamide layer with less resistance. In addition, the smooth surface and decreased pore size of the TiO2 framework contributed to forming a defect-free polyamide layer. As a result, the obtained ceramic-based TFC membrane evinced high permeance of 26.4 L m −2  h −1  bar −1 and excellent salt rejection efficiency, leading to simultaneous improvements compared with the control TFC membrane without the TiO2 framework. Notably, the potential regeneration ability of the ceramic-based TFC membrane could be achieved via facile low-temperature calcination and re-polymerization process due to the varied thermostability between the polyamide layer and the robust ceramic substrate. The operation of regeneration helped to prolong the lifetime and decrease the cost for the ceramic-based TFC membrane. This research provides a feasible protocol to fabricate sustainable ceramic-based nanofiltration membranes with enhanced performance for water treatment. Graphical abstract: Image, graphical abstract